Technological justice: A G20 agenda - Andrés Ortega; Francisco Andrés Pérez; Yarik Turianskyi (Kiel Institute for the World Economy (IfW), 2018)
Technological justice can play an important role within the international system in resolving global challenges and creating a smart and more egalitarian society. Technological and scientific developments are generating huge opportunities for tackling societal challenges. However, the benefits of technology and innovation are unequally distributed, and they tend to cause economic and political disruptions in our societies that widen inequalities within states as well as between countries. Digitalisation and, especially, automation are challenges that must be faced if developing countries are to avoid premature de-industrialization, expulsion from global value chains of the world economy, and the serious damage to their growth paths that would result. The authors propose adopting the concept of 'technological justice' within our societies as a new paradigm for the international system to reconcile technological advances with the societal challenges facing our global society, especially poverty and sustainability; and propose a number of policies and measures by which the G-20 could take on a central role in pushing this major contribution onto the global agenda. The authors participate in the T-20 network of think tanks that facilitates interaction between its members, the public policy community and the general public, being its primary objective to add value to the G20 process with evidence-based public policy proposals on areas of interest for the international agenda.
Keywords: D63; F60; O14; O19; O20; O30; O47; 330; technological justice; automation; premature deindustrialization; developing economies; G20